Time pressure and player disadvantage: Effects on jump performance in simulated matches of well-trained amateur handball players - Teerapong Panichram; Khanita Khumsingsan; Watunyou Khamros (Journal of Coaching and Sports Science, 2026)
Background: At the end of a handball match, when players are physically disadvantaged and pressured by time, their overall fitness declines. This primarily affects their jumping ability, a key skill for scoring points. Aims: This study examined the effects of late-match time pressure and player disadvantage on the jumping performance of well-trained amateur handball players under simulated competition conditions. Methods: Twenty-eight amateur handball players (14 males and 14 females; age 20.00 ± 0.86 years, weight 65.32 ± 11.18 kg, height 169.68 ± 9.56 cm, experience 4.79 ± 2.63 years, and VO2max 40.89 ± 7.67 ml/kg/min) participated in a simulated handball match that replicated the intensity of a simulated game. The match was simulated with a player disadvantage and a score of less than 1 point in the final five minutes. Height jump (HJ), Rate of force development (RFD), and Power (PW) were analyzed using countermovement jumps (CMJ) pre and post competition, along with average heart rate (HR) during the game. Results: HJ, RFD, and PW increased significantly after the competition (P < 0.05), regardless of whether the athlete was on the favored or disadvantaged team. However, no significant differences were found between favored and disadvantaged teams in any of the variables. Conclusion: Jumping performance did not consistently decrease in situations with fewer players and scoring pressure. Furthermore, neuromuscular fitness temporarily increased after intense exercise and a short recovery period.